When Preservation Threatens: Risks to the Integrity of Ancient Islamic Manuscripts in Indonesia - Nyimas Umi Kalsum; Naffa Rachmadini; Kayyisah Safira Amalina; Reza Aprianti (Center for Research and Development of Religious Literature and Heritage, 2025)
This article examines efforts to preserve ancient Islamic manuscripts in Indonesia, with particular emphasis on the risks associated with current conservation practices. Using a qualitative approach, the study analyzes data sourced from social media platforms such as Facebook, Instagram, and relevant websites. The data collection follows a desk-review method, in which content is gathered and categorized based on predefined criteria. This information is then filtered and analyzed to map the threats emerging from preservation efforts. The findings reveal three primary risks in the implementation of manuscript conservation: (1) physical damage resulting from improper preservation methods; (2) the loss of contextual or historical identity of the manuscripts; and (3) the discontinuity or fragmentation of textual content. These risks underscore the need for a comprehensive review of existing government policies and Standard Operating Procedures (SOPs) for manuscript preservation. Such policies must be contextually adapted to Indonesia’s specific environmental and institutional conditions to guide preservation actors effectively.